Proposta curricular do estado de São Paulo : novos papéis ou continuísmo na prática escolar do professor coordenador? - Paula, Adelgício Ribeiro de (2012)
This research has the objective to investigate new roles required of the Teacher Coordinator in the implementation of Curriculum Proposal of the State of São Paulo by the State Secretariat of Education. Our hypothesis is that there are factors in the dynamic that moves the school practice that act as mediators and are strong brands in the daily lives of those working within the school. Sought to verify in school practice of Teacher Coordinator as occur the appropriations of content and procedures required by the standards set by the central organs of the State Department of Education of São Paulo. With focal measures, the State of Sao Paulo seeks to invest resources in a timely manner to combat problems involving the school, however, without to invest in education and structural aspects of society. The Curriculum Proposal presents as purpose, the establishment of a homogeneous curriculum for all schools in its education network. The practice school held in each school is marked by institutional, by differences and the demands of the society around them. It appears that the historical movement of capital expansion prints the movement of society and determines the range of possibilities of the individual in their social action. These premises put to school and workers who operate in it certain prerogatives as the solution of structural and social problems whose origins are external to it. It is observed in the measures and pragmatic actions established under the rhetoric of rupture, old traces of continuity and conservation.